(NsOBRANIE SO^INENIJ W ^ETYREH TOMAH(B; s (NmAR[ TRIDCATOGO GODA(B: [(NpOWESTX(B] / s (N~ASTX (B1s - (NmAKARENKO(B, (NaNTON sEMENOWI^s ((NmOSKWA(B: s (NpRAWDA(B, s, 1987)
(Nw PERWYJ TOM NASTOQ]EGO IZDANIQ WO[LI O^ERK (B"(NmAR[ TRIDCATOGO GODA(B", (NPERWYJ DWE ^ASTI (B"(NpEDAGOGI^ESKOJ PO\MY(B".s
(NpEDAGOGI^ESKAQ PO\MAs
rus
Keywords: (NpOWESTX(B, (NRASSKAZYs; (NrOMANs